(untitled) (Fiep Bulletin - online, 2014)
Since Industrial Revolution, with the adoption of equipments to help human work, there was a reduction of the need of human efforts in the realization of work activities, providing the creation of addictions that provided physical inactivity. For the companies, the sedentary way of life, adopted by the majority of its staff, make high spend of money, as a result of the reduction of productivity produced by the large number of work offs through medical appointments and health issues. In this context, the objective of this study was to analyze possible improvements in the quality of life of sedentary individuals, employees of a private institution of higher education, through the use of therapeutic weight training. The project was realized between September of 2006 and July of 2007, where there were realized 30 sections of therapeutic weight training with a volunteer. The same person was get through an initial functional anthropometric evaluation and after the ending of the application of the method. The results showed that the utilized variables suffered little alterations, what means the necessity of maintaining the program of physical exercises for a longer time.